Procalcitonin-Guided Therapy for Reduction of Antibiotic Use in Patients with Bronchiolitis - Guven, Sirin; Bayoglu, Duygu; Eker, Pinar (Journal of Pediatric Infectious Diseases, 2018)
Objective Procalcitonin (PCT)-guided treatment could reduce antibiotic use in viral lower respiratory tract infections. We evaluated the impact of PCT-guided treatment on antibiotic use in patients hospitalized with bronchiolitis.Study Design A total of 100 patients aged 1 to 24 months old who were hospitalized with bronchiolitis were included in the study. Patients were randomized into two groups: PCT-guided group received an antibiotic treatment based on PCT levels and control group received an antibiotic treatment according to the physician decision.Results Antibiotic use on first day in the PCT-guided group (12%) was found to be statistically significantly lower than in the control group (80%) (p = 0.001; p < 0.05; relative risk [RR]: 29.33; 95% confidence interval [CI]: 9.77–88.03). On the third day, antibiotic use was statistically significantly lower in the PCT-guided group (16%) than in the control group (40%) (p = 0.014; p < 0.05; RR: 3.5; 95% CI: 1.36–9).Conclusion We suggested that PCT guidance will have important contributions to reduce antibiotic use in children with bronchiolitis. Particularly in countries with higher antibiotic prescription rates, this strategy may have implication for reducing the development of antibiotic resistance and side effects due to disturbance of microbiota.
Keywords: bronchiolitis; children; procalcitonin